The effect of using BCPAP in the management of Respiratory Distress (Texas Journal of Medical Science, 2023)
In the developing world, one of the biggest cause why infant die is respiratory distress. A noninvasive respiratory support technique called bubble continuous positive airway pressure (BCPAP) is used to treat neonates who are experiencing respiratory distress. It was originally mentioned in 1971 as a way to help premature newborns' respiration. BCPAP is a less invasive method of providing respiratory assistance to newborns than mechanical ventilation. Method: 63 babies with respiratory distress were put on BCPAP as part of a clinical trial study that was undertaken at Al-Forat Al-Awsat Teaching Hospital in An'najaf city from February 1 to June 30, 2018. Results: It was shown that although 38 patients (60.31%) with respiratory distress were helped and effectively weaned off of BCPAP, CPAP failed to help 25 patients (39.68%) with respiratory distress, and they died as a result. Conclusion: BCPAP was beneficial in treating respiratory distress.